The Relevance of Taha Abdurrahman's Islamic Education Thought to the Challenges of Modern Education: (Relevansi Pemikiran Pendidikan Islam Taha Abdurrahman terhadap Tantangan Pendidikan Modern) - Apriliana, Milda (Faculty of Teacher Training and Education, Palangka Raya University, Central Kalimantan, Indonesia. Pos Code 73112, 2026)
Contemporary education is increasingly dominated by instrumental rationality, technocratic management, and efficiency-oriented approaches, which often marginalize ethical, spiritual, and moral dimensions. In Islamic education, this condition creates a tension between normative ideals that emphasize moral and spiritual formation and the uncritical adoption of modern educational paradigms. This study aims to examine the relevance of Taha Abdurrahman’s Islamic educational thought in addressing the challenges of modern education, particularly moral crisis, secularization, and the reduction of education to technical skill transmission. Using a qualitative library research approach, the study analyzes primary works of Taha Abdurrahman and relevant secondary literature on Islamic education, philosophy of education, and modernity. Data were examined through content analysis with a philosophical-critical perspective to identify and synthesize key concepts such as ethical rationality (al-‘aql al-akhlāqī), moral responsibility (amanah), and spiritual consciousness. The findings indicate that Taha Abdurrahman offers a coherent ethical-spiritual framework that critiques instrumental rationality and secularized education while proposing an integrative model that unites knowledge, ethics, and spirituality. His thought highlights education as a process of moral and character formation rather than mere cognitive achievement. The study implies that Islamic education can benefit from reorienting its goals, curriculum, and pedagogical practices toward ethical and spiritual integration. In conclusion, Taha Abdurrahman’s educational philosophy provides a relevant conceptual foundation for renewing Islamic education in responding to modern challenges, while maintaining its moral identity and humanistic orientation, and offers direction for further theoretical and applied research.